Lactoferrin on Physiological Characteristics and Intestinal Microorganisms in Anemic Rats - Suhad Khalid Sgheer; Tuqa Sabbar Rahi (Academia Open, 2026)
General Background: Iron is essential for hematopoiesis, immune competence, and growth, and its deficiency leads to anemia with systemic consequences. Specific Background: Lactoferrin, an iron-binding glycoprotein, exhibits hematopoietic, immunomodulatory, and antimicrobial activities that may benefit anemia and gut microbiota balance. Knowledge Gap: Experimental evidence comparing purified and commercial lactoferrin on hematological indices and intestinal microbial populations in anemic models remains limited. Aims: This study evaluated the effects of purified and commercial lactoferrin on blood parameters and gut microorganisms in anemic female rats. Results: Lactoferrin administration increased red blood cells, hemoglobin, and platelets, reduced white blood cell counts, enhanced lactic acid bacteria, and decreased coliforms, Staphylococcus spp., and Enterococcus spp., with strongest effects at 30 µg/kg purified lactoferrin, while Salmonella showed minimal change. Novelty: The study demonstrates dose-dependent superiority of purified lactoferrin over commercial forms. Implications: Purified lactoferrin represents a promising dietary supplement for anemia management and gut health modulation.Keywords : Lactoferrin, Iron Deficiency Anemia, Hematological Parameters, Gut Microbiota Modulation, Female Albino RatsHighlight : Purified supplementation significantly increased erythrocyte, hemoglobin, and platelet indices in anemic female models. Dose-dependent treatment reduced leukocyte counts, indicating pronounced immunomodulatory activity. Beneficial gut bacteria increased, while coliforms, staphylococci, and enterococci declined after intervention.